Key Gene and Functional Pathways Identified in Unexplained Recurrent Spontaneous Abortion Using Targeted RNA Sequencing and Clinical Analysis - Gu, Heng; Li, Longyu; Du, Mengxuan; Xu, Hang; Gao, Mengge; Liu, Xiaohua; Wei, Xiangcai; Zhong, Xingming (Frontiers in Immunology, 2021)
Identifying the mechanisms underlying unexplained recurrent spontaneous abortion (URSA) can help develop effective treatments. This study provides novel insights into the biological characteristics and related pathways of differentially expressed genes (DEGs) in URSA. Nineteen patients with URSA and three healthy fertile women with regular menstruation (control group) were recruited. RNA was extracted from the two groups to determine the differential expression of immunoregulatory gene sequences. Gene ontology (GO) and Kyoto Encyclopaedia of Genes and Genomes (KEGG) enrichment analyses were used to identify the biological functions and pathways of the identified DEGs. A protein-protein interaction (PPI) network was constructed using the STRING database. Furthermore qRT-PCR and ELISA were performed to validate the differential expression of the hub genes. We also explored the regulatory mechanism of Th1/Th2 imbalance. A total of 99 DEGs were identified, comprising 94 upregulated and five downregulated genes. Through GO analysis, nine immune cell function-related clusters were selected, and genes with significant differential expression were primarily enriched in eight immune regulatory functions related to the KEGG signaling pathway. Subsequently, five hub genes (TLR2, CXCL8, IFNG, IL2RA, and ITGAX) were identified using Cytoscape software; qRT-PCR validated the differential expression among the hub genes, whereas ELISA revealed a significant difference in extracellular IFN-γ and IL-8 levels. The levels of Th1 (IFN-γ) and the Th1/Th2 ratio were higher in the peripheral blood of URSA patients than in control group patients. These findings suggest that the occurrence of URSA may be associated with the abnormal expression of some specific immunoregulatory genes involved in T cell activation and differentiation. Among the identified DEGs, IFNG may play a key role in regulating maternal immune response. Although further validation is required, our data provide an important theoretical basis for elucidating the pathogenesis of recurrent spontaneous abortion.